Two‐step hydrothermal fabrication of Na0.23TiO2 nanofibers and enhanced photocatalysis after loaded with gold or silver determined by surface potentials - Wang, Jing‐Zhou; Chen, Qi‐Wen; Zhou, Jian‐Ping; Lei, Yu‐Xi; Menke, Neimule (International journal of energy research, 2019)
Summary Pure Na0.23TiO2 nanofibers were fabricated by a two‐step hydrothermal method after a series of experiments. Na0.23TiO2 is a direct bandgap semiconductor and exhibits a strong photodegradative ability for RhB, which is difficult to be degraded. The photodegradative activity is much enhanced after loaded noble metal Au or Ag nanoparticles on Na0.23TiO2 nanofibers by a chemical bath deposition method. Hot electrons are generated in metal nanoparticles through a localized surface plasmon (LSP) process under light illumination and then diffuse to a semiconductor and reduce the surface potential, which is detected directly by a scanning Kelvin probe microscopy (SKPM). The high electromagnetic field induced by the LSP resonance and strong coupling between noble metal and Na0.23TiO2 are beneficial for the utilization of visible light, electron produce, charge transportation, and separation, as a result, promoting the activity of semiconductor‐based photocatalysts. This work supplies an effective method to directly probe the surface plasmon and highlights the application of Na0.23TiO2 in photocatalysis.